الاختیار الامثل لالوان غرفة الطفل وفق بعض المتغیرات - م.م.سھام محسن امویلح الربیعي (College of Education for Women, 2019)
Color is perhaps the most important element in art because it is what first attracts attention when looking at any thing or any work of art.the important of colors is clear in the life of every one of the people. A good color scheme in all aspect s of life is a clear indication of a highly developed society and nation. It also has appositive effect on the individual s by providing feeling s of joy and comfort - such feeling encourage hard work and productivity whether at home. At school or at work. A study of childhood and attention of the criteria by which to measure the progress of society and its development as the interest in childhood is in fact interesting Bmstqubla the whole nation. The current research sheds light on the importance of colors and their role in the lives of children and variables that reflected on their behavior and their actions in life. The importance of the subject. The researcher chose to kindergarten aged children (4-6 years), which formed in the this stage, the first seed of the aesthetic taste and understanding of what the resentment of the size and color of the children. And the tendency of the child in this age to use the colors of the design and choice of colors, favorite games has. Therefore, parents must take into account the environment variable and gender when choosing a favorite color of Alatvalhm.